Civic Engagement, Legal Status, and the Context of Reception: Participation in Voluntary Associations among Undocumented Immigrants in California. (April 2021) - Beck, Kevin; Shklyan, Karina
For undocumented immigrants, processes of integration are contingent on the qualities of their local context. A lack of legal status may require them to strategically manage their presence in order to avoid detection that could lead to deportation. The authors ask how the need to mask one's legal status affects the civic integration of undocumented immigrants. Drawing primarily on data from the California Health Interview Survey, the authors estimate the probability of participation in voluntary associations for undocumented immigrants. They naturalized immigrants and find that undocumented immigrants exhibit a lower rate of participation but that this low rate of participation is unlikely the result of their legal status. The findings also show that undocumented immigrants are less likely to participate in voluntary associations if they live in counties where large shares of voters cast votes for Donald Trump in the 2016 presidential election.